2020
DOI: 10.1037/sah0000179
|View full text |Cite
|
Sign up to set email alerts
|

Testing active learning workshops for reducing implicit stereotyping of Hispanics by majority and minority group medical students.

Abstract: The present research tested if having first-year medical students complete active learning workshops would reduce their implicit stereotyping of Hispanics as medically noncompliant. The workshops were tested with 78 majority (White) group, 16 target minority (Hispanic, African American, and American Indian) group, and 42 nontarget minority (Asian American and foreign-born students from East Asia and Southeast Asia) group students in the 2018 and 2021 classes in the American Southwest. Prior to the workshops, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
(70 reference statements)
0
33
0
Order By: Relevance
“…34 Bias training has been effective in reducing implicit bias and changing behavior among health care professionals. 35,36 Small systemic changes may also improve health equity. 12 Participants in this study identified patient photographs and descriptions of children as potential sources of bias.…”
Section: Discussionmentioning
confidence: 99%
“…34 Bias training has been effective in reducing implicit bias and changing behavior among health care professionals. 35,36 Small systemic changes may also improve health equity. 12 Participants in this study identified patient photographs and descriptions of children as potential sources of bias.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research testing the effectiveness of implicit bias reduction strategies among medical students and physician providers has primarily focused on vulnerable racial and ethnic groups [51]. Promising strategies shown to be effective in reducing implicit racial and ethnic biases in medical students include those which seek to increase bias awareness [52], perspective-taking [53], and seeking counter-stereotypic information [54]. A study of 3547 students from 49 U.S. medical schools found that completing a racial IAT as part of formal curricula was associated with decreases in implicit racial bias from the first to last semester of school [52].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this proposition, a 2019 study showed that this habit-breaking approach was successful in decreasing implicit stereotyping of Latinxs among white medical students in the USA. 21 In fact, implicit bias training that does not teach concrete strategies to health-care providers could potentially have unintended harmful consequences. Specifically, increased awareness of someone's own implicit bias without specific strategies might result in increased anxiety and ultimately avoidance (eg, being discouraged to work at clinics that serve patients from marginalised social groups), withdrawal (eg, having shorter visits with marginalised patients), or overcome-pensation (eg, being overly friendly, which could be perceived by marginalised social groups as ingenuine and unauthentic).…”
mentioning
confidence: 99%